2019
DOI: 10.1111/aogs.13671
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of pregnancies with reduced fetal movements: A retrospective cohort study

Abstract: Introduction The objective of this study was to examine the outcomes and interventions in pregnant women presenting with a perception of reduced fetal movements (RFM), and to determine if repeated episodes of RFM increase the risk of adverse outcomes. Material and methods This was a retrospective cohort study conducted in six NHS hospitals within the Thames Valley network region, UK and one neighboring hospital, an area with approximately 31 000 births annually. All women with a primary presentation of perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
(42 reference statements)
3
13
0
Order By: Relevance
“…However, our results suggest that risk of stillbirth may be increased among women with 2 or more presentations of DFM compared with women with 1 presentation. Consistent with results from other studies, 14,16,[33][34][35] we found that DFM was associated with higher odds of planned early term birth, IOL, and emergency cesarean delivery for intrapartum fetal compromise and lower odds of vaginal birth. Additionally, we found that women with DFM had higher rates of SGA births.…”
Section: Discussionsupporting
confidence: 91%
“…However, our results suggest that risk of stillbirth may be increased among women with 2 or more presentations of DFM compared with women with 1 presentation. Consistent with results from other studies, 14,16,[33][34][35] we found that DFM was associated with higher odds of planned early term birth, IOL, and emergency cesarean delivery for intrapartum fetal compromise and lower odds of vaginal birth. Additionally, we found that women with DFM had higher rates of SGA births.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, primiparous women were 1.4 times more likely to present with RFM compared to multiparous women during COVID. As previous work have repeatedly demonstrated no significant differences in parity with regards to attendances for RFM [ 22 , 23 ], we believe our findings to be true.…”
Section: Discussionsupporting
confidence: 74%
“…Similar to our findings, a recent published study from UK showed no association between recurrent RFM episodes and increased adverse neonatal outcome, but an association with higher induction rates. 17 Furthermore, a liberal induction policy starting from 37 weeks for the women with recurrent RFM showed no benefit. 20 Several large projects such as "Each Baby Counts" and the AFFIRM study are trying to improve information and knowledge about IUFD but have not been successful in preventing it.…”
Section: Discussionmentioning
confidence: 99%